CORAK PENAFSIRAN JALÄ€LUDDÄªN AL-SUYÅªá¹¬Äª: STUDI ATAS KITAB TAFSÄªR JALÄ€LAYN - Syarwani dan Adrika Fithrotul Aini (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
TafsÄ«r JalÄlayn is one among other exegetical works commonly used in Indonesia, particularly in pesantrens.Â It is well-known that this work is relatively concise and straightforward that people can easily understand it.Â This paper attempts to discuss the authors of the work with a focus on JalÄluddÄ«n al-SuyÅ«á¹Ä« who completed andÂ continued the work of JalÄluddÄ«n al-Maá¸¥allÄ«. It will examine al-SuyÅ«á¹Ä«â€™s types and methods in his interpretationÂ work after the latter.Keywords: al-SuyÅ«á¹Ä«, Tafsir al-JalÄlayn, Tipologi TafsÄ«r